Discourse Of Flowers In Contemporary Betawi Culture - Dadan Iskandar, Dadan Iskandar; Feni Fasta, Feni Fasta (2015)
Discourse about flowers means discourse with symbol. It was constructed to serve the needs of a culture to be a symbol in a tradition. This tradition can gradually find themselves in different modifications according reception times. In Betawi people for example, the delivery of messages through the depth of flowers despite its meaning can not be changed. Now, the original of a culture of the ritual to Betawi wedding ceremony is rarely seen among the community. While the information and knowledge about communication symbol of the flowers of Betawi culture is still not widely known. Therefore, this research would like to explain in more detail about flowers and their meanings of the communication symbol in Betawi culture, especially for the citizens of Betawi Rawa Belong, Jakarta Barat. Flowers in question are Melati, Kenanga, Cempaka, dan Kamboja